Study on I/O response time bounds of network storage systems - CUI Bao-jiang1; LIU Jun2; WANG Gang2; LIU Jing2 (Tongxin xuebao)
In order to predict and improve the performance of networked storage systems,the relationship was explored between the system I/O response time and its performance factors by quantitative analytical method.Through analyzing data flow in networked RAID storage system,we established its analytical model utilizing closed queuing networks and studied on performance bounds of the system I/O response time.Experimental results show that the theoretical bounds are found to be in agreement with the actual performance bounds of the networked RAID storage system and reflect the dynamic trend of its actual performance.Furthermore,we conclude that the CPU processing power and cache hit rate of the server at the storage center are the key factors affecting the I/O response time,as the concurrent jobs are lower.